Ultrasonic Transducers with a very short impulse response - Optel sp. z o.o. R&D company (Archives of Acoustics)
We offer a new type of Ultrasonic Transducers with a very short impulse response, for nondestructive testing and all other purposes, where broadband transfer function, high amplitude of the pulse, high sensitivity and low cost are required.The idea of this type of transducer (a patent application has been submitted) was born as a spin-off from our biometric project (see our paper in this issue).